(3LeY GdLhGeY aj Gdabg GdMfHdis - (3jhSa Hf MSf Hf CMeO Hf MSf Hf YHO GdgGOj GdUGdMj, LeGd GdOjf, GHf GdeHQO,J (B909 (3g` s
(3ChdgG (B:s
(3aUd (B: (3aEf hba Ydi fjI Ch Hfi adGf agh dPchQge NGUI fU Ydjg s
(3HgG fXGe GdJYbjHIs
(3djS dg BNQ jfJgi Hg GdLRA dGVWQGH ChQGbgG hGNJdGdgGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B225 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B289s
(3JHUQGJ GdCUd (B:s
(3HgG NQe s
Keywords: (3Gdabg GdMfHdjs